Development of a rapid diagnostic method for identification of Staphylococcus aureus and antimicrobial resistance in positive blood culture bottles using a PCR-DNA-chromatography method. Issue 6 (June 2016) - Ohshiro, Takeya; Miyagi, Chihiro; Tamaki, Yoshikazu; Mizuno, Takuya; Ezaki, Takayuki
Abstract: Blood culturing and the rapid reporting of results are essential for infectious disease clinics to obtain bacterial information that can affect patient prognosis. When gram-positive coccoid cells are observed in blood culture bottles, it is important to determine whether the strain is Staphylococcus aureus and whether the strain has resistance genes, such as mecA and blaZ, for proper antibiotic selection. Previous work led to the development of a PCR method that is useful for rapid identification of bacterial species and antimicrobial susceptibility. However, that method has not yet been adopted in community hospitals due to the high cost and methodological complexity. We report here the development of a quick PCR and DNA-chromatography test, based on single-tag hybridization chromatography, that permits detection of S. aureus and the mecA and bla Z genes; results can be obtained within 1 h for positive blood culture bottles. We evaluated this method using 42 clinical isolates. Detection of S. aureus and the resistance genes by the PCR-DNA-chromatography method was compared with that obtained via the conventional identification method and actual antimicrobial susceptibility testing. Our method had a sensitivity of 97.0% and a specificity of 100% for the identification of the bacterial species. For the detection of the mecA gene of S. aureus, the sensitivity was 100% and the specificity was 95.2%. For the detection of the blaZ gene of S. aureus, the sensitivity was 100% and the specificity was 88.9%. The speed and simplicity of this PCR-DNA-chromatography method suggest that our method will facilitate rapid diagnoses.